Investigation of paradoxical structures in Hafez's Ghazals - Maedeh Shegheft; Yadollah Shokri; Mohammad Rezaei; Rasool Rasoolipour (مطالعات زبانی و بلاغی)
The paradox in literature is one of the most widely used measures to create space, meanings, as well as the creation of the imagination. The history of Persian poetry shows that not only the literary elements or arrangements have evolved throughout history, but they have also become more complex. Although in the Iraqi style, perhaps no poet as much as Hafiz in his set of sonnets has embraced paradoxical compositions. However, the two semantic and hybrid types of paradox in Hafiz's poetry not only serve as an instrumental or literary industry but also structurally form the inferior space between the two human-divine talents of Hafiz's poetry subjects. What this means is that paradoxes, in addition to playing their role as aesthetic delusions, have a double application in the formation of a paradoxical space in general. The present paper attempts to study the paradoxical structures in Hafiz's sonnets by examining the paradoxical structures of how the paradoxical thing, apart from its intended nature, can function structurally in the creation of new spaces in poetry. The results of the discussion indicate that it is important to note that many similar industries also serve as a structure in the poetry of conflict. Considering that the structural study of paradoxes is separate from the study of paradoxes one by one, it can be a new approach to the relationship between linguistic-rhetorical and conceptual categories in Hafez's poetry. In this study, we see how paradoxes transcend their own status as an aesthetic element and, in proportion to each other, produce a system or structure in which the aspects of good and evil, heroes and anti-heroes, and Truth and falsehood are also opposed.